Analisis Keberhasilan Implementasi Kebijakan Rekam Medis Elektronik: Perspektif Struktur Birokrasi - Sugiarto, Puput; Purnami, Cahya Tri; Jati, Sutopo Patria (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2025)
All healthcare facilities are required to implement Electronic Medical Records (EMR). The implementation of this policy faces various challenges, one of which is the bureaucratic structure in hospitals. This study aims to analyze the success of EMR implementation with a focus on the aspect of bureaucratic structure based on George Edward III's policy implementation model. This research uses a qualitative method with a case study approach conducted in three type C hospitals. Data were collected through in-depth interviews, non-participatory observations, and documentation studies involving 13 informants, which included the head of the medical records installation, the head of the information technology installation, medical recorders and health information, information technology officers, and the head of the medical services department. Hospitals that form special teams for EMR implementation have more controlled and efficient processes compared to hospitals that rely on existing organizational structures. The presence of a special team facilitates coordination, socialization, and training of healthcare personnel in the use of EMR. Meanwhile, hospitals that do not form a special team experience obstacles in coordination and delays in system adoption, despite receiving support from the system developers. An effective bureaucratic structure plays a crucial role in the successful implementation of EMR. Therefore, hospitals are advised to form a special team for the implementation of EMR to accelerate system adoption and improve the quality of healthcare services.